2015
DOI: 10.3390/jpm5040389
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an mHealth Medication Regimen Self-Management Program for African American and Hispanic Uncontrolled Hypertensives

Abstract: African Americans and Hispanics have disproportionate rates of uncontrolled essential hypertension (EH) compared to Non-Hispanic Whites. Medication non-adherence (MNA) is the leading modifiable behavior to improved blood pressure (BP) control. The Smartphone Medication Adherence Stops Hypertension (SMASH) program was developed using a patient-centered, theory-guided, iterative design process. Electronic medication trays provided reminder signals, and Short Message Service [SMS] messaging reminded subjects to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
182
0
10

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(192 citation statements)
references
References 59 publications
(96 reference statements)
0
182
0
10
Order By: Relevance
“…One of mHealth's strengths is its ability to leverage the existing mobile technology infrastructure and the ubiquity of the mobile phone across populations and sub-groups. Previous research has corroborated the high prevalence of smartphone usage among Blacks as well as Hispanics and indicated the value of mHealth in managing chronic illness [11].…”
Section: Technology As a Means Of Engagementmentioning
confidence: 65%
See 1 more Smart Citation
“…One of mHealth's strengths is its ability to leverage the existing mobile technology infrastructure and the ubiquity of the mobile phone across populations and sub-groups. Previous research has corroborated the high prevalence of smartphone usage among Blacks as well as Hispanics and indicated the value of mHealth in managing chronic illness [11].…”
Section: Technology As a Means Of Engagementmentioning
confidence: 65%
“…Electronic or digital health encompasses a wide range of technologies that are used for healthcare, health informatics, health education, and health promotion; and Mobile health (mHealth)-the application of wireless technology to promote wellness and information provision between healthcare and individuals-is rapidly gaining attention in both preventive medicine and chronic illness management [11]. One of mHealth's strengths is its ability to leverage the existing mobile technology infrastructure and the ubiquity of the mobile phone across populations and sub-groups.…”
Section: Technology As a Means Of Engagementmentioning
confidence: 99%
“…The publication year of the studies ranged from 2012 to 2017 (see Table 1). Most studies (n=11) were conducted in the US [24][25][26][27][28][29][30][31][32] and Canada [33,34], while seven were carried out in European countries, including France [35], Sweden [36][37][38], Spain [39,40] and Italy [41]. The remaining three studies were conducted in China [42,43] and South Korea [44. Nine studies were randomised controlled trials (RCTs) [24,25,27,28,30,[33][34][35]42], ten were nonrandomised studies [26,29,31,32,37,[39][40][41]43,44], and two were qualitative studies [36,38].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Participants' average age ranged from 42.4 years [27] to 69.5 [42] years. The population groups of the studies included individuals with hypertension [24][25][26][27][28][29][30]32,[36][37][38][39][41][42][43][44], metabolic syndrome risk factors [34], and obstructive sleep apnoea with high cardiovascular risk [35], as well as overweight individuals [31]. Of the 21 included studies, 5 reported to have used behavioural theories, such as selfdetermination theory [24,26,27], motivational interviewing [30] and theory of planned behaviour [43] to underpin and guide the intervention methods and/or the development of the technology.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation